Workplace boredom as an empowering experience: a psychoanalytic reconceptualization of boredom and identity in organizations. Issue 2 (4th March 2022) - Driver, Michaela
ABSTRACT: The study develops a psychoanalytic perspective on boredom as an important resource for narratively constructing the self with significant implications for how functional or dysfunctional it is. By employing a Lacanian framework, the study suggests that prior research, investigating boredom mainly as a widespread individual problem in organizations, has emphasized one aspect of how boredom interacts with identity, namely its imaginary function. While research emphasizing more constructive aspects of boredom, seems to emphasize boredom's symbolic function. The study explores how we can better understand and facilitate the latter, as it has the potential to unsettle identity work, and, thereby, empower individuals to connect differently to themselves and others in transformative ways. Specifically, the study suggests that the extent to which boredom serves empowering functions depends on the discursive movement that individuals undertake as they engage in identity work. Implications of this and other findings for future research are discussed.